Evaluation of critical congenital heart disease from 2018 to 2020 in Turkey: a retrospective cohort study - Nilgün Çaylan; Sıddika Songül Yalçın; Başak Tezel; Oben Üner; Şirin Aydin; Fatih Kara (BMC Pregnancy and Childbirth, 2023)
Abstract Background The aim of this study is to examine the features of critical congenital heart disease (CCHD). Methods The study was planned as a retrospective cohort study. Data for the study were obtained through national data collection systems and 2018–2020 CCHD cohort was established. In this study, we divided the patients into two groups: Group 1 included seven primary target diseases of the newborn CCHD screening program and Group 2 included secondary target diseases. Results There were 9884 CCHD cases, with a prevalence of 27.8 per 10,000 live births. Of the cases 44.4% were in Group 1 (12.3 per 10,000) and 54.8% were in Group 2 (15.2 per 10,000). Of all cases 55.5% were male and the female/male ratio was 1/1.2. While 21.8% of the cases were premature, 23.0% were babies with low birth weight (LBW), 4.8% were born from multiple pregnancies. The highest prevalence of CCHD was found in LBW (84.8 per 10,000), premature infants (57.8 per 10,000) (p < 0.001). The fatality rate in the cohort was 16.6% in the neonatal period, 31.6% in the first year of life respectively. The mean estimated survival time in the birth cohort was 40.0 months (95% CI: 39.5–40.6). The mean survival time for Group 1 diseases was 33.4 months (95% CI: 32.5–34.2), while it was 45.4 months (95% CI: 44.7–46.0) for Group 2 diseases (p < 0.001). Preterm birth, LBW, maternal age and region were evaluated as factors associated with mortality risk. Conclusion This study showed that CCHDs are common in Turkey and mortality rates are high. There are regional differences in CCHD both prevalence and survival. Improving prenatal diagnosis rates and expanding neonatal CCHD screening are of key importance.